Formation of the Mechanism for Conducting Internal Audit at the Railway Transport Enterprises - Obydiennova, Tetiana; Chobitok, Viktoriya; Dudnieva, IuliÑ–a (International Journal of Engineering and Technology, 2018)
The article deals with the issues of conducting internal audit at the railway transport enterprises. The difference between the concepts of â€œinternal auditâ€ and â€œinternal controlâ€ is defined. The main principles and objectives of the internal audit, information base and main tasks are revealed. The authorsâ€™ classification of types of internal audit at the enterprises of railway transport is offered. It has been determined that for conducting internal audit at the enterprises of railway transport, it is necessary to use general scientific and special methods and techniques. The authors gave a comprehensive description and specific recommendations for their application. The goals of the internal audit department (committee) at the enterprises of railway transport are singled out separately. It is determined that during the work the internal audit department receives a lot of information from internal and external sources. The authorsâ€™ mechanism of conducting internal audit at the enterprises of railway transport is prepared.Â Â